2023
DOI: 10.1021/acs.est.2c07462
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Electrocatalytic Hydrodechlorination through Interfacial Microenvironment Modulation

Abstract: Electrochemical reduction (ER) is a promising approach to safely remove pollutants. However, sluggish reaction kinetics and significant side reactions considerably limit the applicability of this green process. Herein, we uncovered the previously ignored role of interfacial hydrophilicity in determining the ER performance through electron microscopy observations, contact angle (CA) analysis, and electrochemical measurements. A Pd/C electrocatalyst forms dense nanopores on the electrode surface, rendering it hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 41 publications
5
31
0
Order By: Relevance
“…As illustrated in Figure S26, three peaks were observed in the potential range of −1.2 to −1.0 V, −0.85 to −0.75 V, and −0.4 to 0.3 V, corresponding to H 2 , H* abs (H* absorbed in the catalyst lattice), and H* ads (H* adsorbed on the catalyst surface), respectively. , As shown in Figure S27, the Tafel slopes of Co–N/C and N/C were 141 and 116 mV dec –1 , respectively. Compared with N/C, Co–N/C showed an increase in the Tafel slope, demonstrating the HER-suppressing activity of Co–N/C . Co–N/C enhanced the dissociation of water and promoted the generation of H*.…”
Section: Resultsmentioning
confidence: 94%
“…As illustrated in Figure S26, three peaks were observed in the potential range of −1.2 to −1.0 V, −0.85 to −0.75 V, and −0.4 to 0.3 V, corresponding to H 2 , H* abs (H* absorbed in the catalyst lattice), and H* ads (H* adsorbed on the catalyst surface), respectively. , As shown in Figure S27, the Tafel slopes of Co–N/C and N/C were 141 and 116 mV dec –1 , respectively. Compared with N/C, Co–N/C showed an increase in the Tafel slope, demonstrating the HER-suppressing activity of Co–N/C . Co–N/C enhanced the dissociation of water and promoted the generation of H*.…”
Section: Resultsmentioning
confidence: 94%
“…Here we have considered only one of the HFOs known to produce CF 3 CHO, 10,11 and by extension, HFC-23; however, emissions of other CF 3 CHO-producing HFOs are also projected to grow substantially in the coming decades. 34 Our results imply a potential need to reconsider the labelling of HFOs as "low-GWP" alternatives, with more precise quantication of the HFC-23 quantum yield from CF 3 CHO critical for understanding the true climate impact of HFO use.…”
Section: Discussionmentioning
confidence: 90%
“…Liu et al conducted surface-enhanced Raman spectroscopy and found that H ads * is the primary active species in EHDC . Additionally, the H* contribution could be determined by analyzing the electron spin resonance characteristic peaks ( e.g., nine characteristic peaks) or by scavenger for H* radicals. , Lou et al used tert -butanol as an H* scavenger to remove H* from EHDC and quantified the contribution of H* …”
Section: Mechanism Of Electrocatalytic Hydrodechlorinationmentioning
confidence: 99%